2006
DOI: 10.1021/bi060600w
|View full text |Cite
|
Sign up to set email alerts
|

Defining Lipid-Interacting Domains in the N-Terminal Region of Apolipoprotein B

Abstract: Apolipoprotein B (ApoB) is a nonexchangeable apolipoprotein that dictates the synthesis of chylomicrons and very low density lipoproteins. ApoB is the major protein in low density lipoprotein, also known as the "bad cholesterol" that is directly implicated in atherosclerosis. It has been suggested that the N-terminal domain of apoB plays a critical role in the formation of apoB-containing lipoproteins through the initial recruitment of phospholipids in the endoplasmic reticulum. However, very little is known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
51
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 51 publications
7
51
0
Order By: Relevance
“…Putting these findings into context with other studies of the ␤␣1 superdomain, such as the LV structure of the ␤␣1 superdomain (8 -11, 13, 28), in vitro lipid binding assays (12,14,17,23,29), the conserved sequence motifs (9,30), and apoB C-terminal truncation secretion (31-33), we have developed a more detailed mechanism of initial co-translational apoB lipid binding (see Fig. 14), using the TPs we report here as a road map.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Putting these findings into context with other studies of the ␤␣1 superdomain, such as the LV structure of the ␤␣1 superdomain (8 -11, 13, 28), in vitro lipid binding assays (12,14,17,23,29), the conserved sequence motifs (9,30), and apoB C-terminal truncation secretion (31-33), we have developed a more detailed mechanism of initial co-translational apoB lipid binding (see Fig. 14), using the TPs we report here as a road map.…”
Section: Discussionsupporting
confidence: 58%
“…The hydrophilic face is predicted to form salt-bridge interactions with the C-terminal half of the ␣HD (8,9). By itself, the C-sheet sequence clears 1,2-dimyristoyl-snglycero-3-phosphocholine vesicles extremely rapidly (12). The A-sheet is less homologous to LV than the rest of the ␤␣1 domain and is only partially modeled.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Third, Rava et al (60) demonstrated that MTP is not required for the secretion of apoB18. Relevant to this finding are studies demonstrating that apoB17 readily associates with phospholipids (61)(62)(63). Assuming that PL transfer activity of MTP is sufficient for the formation of primordial apoB particles, it is reasonable to expect that the secretion of apoB18 in COS cells would increase, at least partially, by the expression of Drosophila MTP; this was not observed by Rava et al (60).…”
Section: Discussionmentioning
confidence: 91%